The Effectiveness of Ivermectin on the Risk of Mortality in COVID-19 Patients: A Meta Analysis - Ayu Trisni Pamilih; Didik Gunawan Tamtomo; Bhisma Murti (Masters Program in Public Health, 2021)
Background: The Coronavirus Disease 2019 (COVID-19) has become the highest priority of global pandemic. New and repurposed drugs are being tested on mild to moderate levels of COVID-19 to help suppress transmission of the virus. Ivermectin is one of the repurposed drugs with known safety records with more than 2.5 billion doses dispensed in the past. This study aims to estimate the effectiveness of ivermectin in reducing the risk of mortality in COVID-19 patients based on the results of a number of previous similar studies.Subjects and Method: This study is a systematic review and meta-analysis. This study used secondary data in the form of data from previous study results. A systematic and comprehensive database search was carried out through several databases including: PubMed, Science Direct, Google Scholar, and Springer Link. Analysis of this study was using RevMan 5.3 software. This study used the eligibility criteria with the PICO model, populations: covid-19 patients, intervention: ivermectin administration, comparison: patients without ivermectin, outcome: mortality in COVID-19 patients. The inclusion criteria used were full paper in English and Indonesian with a randomized controlled trial, including the number of deaths, and the primary study was conducted in a hospital. The keywords used to search the database were